2011 Tahrir Square Demonstrations in Egypt: Semantic Structures That Unify And Divide. Issue 2 (31st December 2020) - Khatib, Hakim
Abstract: While literature has focused on political, economic and social indicators to understand the shifts, or rather the fragmentationsof the political scene in Egypt, the role of semiotic constructions was significantly if not totally neglected. This article investigates whether the demands and messages produced by protesters of Tahrir Square in January 2011 have played a role in processes of unification and fragmentation of Egyptians. Following Roland Barthes' (2006) and Chris Barker's (2011) methods of linkage to define the meanings suggested by the commentaries that appeared on the banners during the demonstrations of 2011 in Egypt, this article argues that the demands, messages and meanings produced and suggested throughout the demonstrations of 2011 in Egypt have not been responded to accordingly; therefore they have created a complicated transformational process that is replete with polarization. The messages, which brought people to collectively act against authoritarianism, are the same messages that have outflanked them. An Egyptian profound debate to define the signified meanings at Tahrir Square has not occurred in Egypt leaving a tremendous space for interpretations and conflicting perceptions.